Problématique Des Refoulements Des Produits De La Pêche Exportés Par Le Maroc Et Leur Impact Economique - Said Dahani; Hajar Chouarfa; Ahmed Bousselhami; Nourredine Bouchriti (European Scientific Journal, ESJ, 2017)
In this paper, we dealt with the problem of the rejections of fishery products exported to other countries via Morocco and their economic impact. The study was conducted using a survey by exporters of the fishing industry. The analysis of data shows that backflows can be caused by different sanitary or documentary reasons. Also, the health profile for the main species can be assessed by a criticality matrix "fish species: hazard: commodity". The determinants of the rejections of exported fish products were analyzed by a multiple regression. This econometric technique is considered valuable in our study to evaluate the impact of a set of variables on the cost of the rejections of fishery products. The rejections of fishery products have a tremendous impact both on fish business operators as well as for the competent authorities. Hence, there is the need to control the various health hazards associated with fishery products by professionals. This was done by adopting plans for health control within their establishments and for the strengthening of official control by the competent authority in a coregulation framework.